Rubber (Hevea brasiliensis) seedlings growth performance in response to various rates of N and P fertilizers - Saufe, Nur Aqilah (2015)
The competitiveness with the other rubber producer has led the Rubber National Key Economic Area (NKEA) to drive the sectors’ growth with acceleration of the replanting and new planting of rubber. Replanting has become critical as there are already 40,000 ha of old rubber trees that will be replanted continuously while new planting of 30,000 ha per year will be conducted within 5 years. Hence, adequate nutrition for rubber seedlings is considerably necessary to enhance growth and development of the rubber seedlings due to increasing demand for replanting purposes. Therefore, this experiment was carried out to evaluate the rubber seedling growth performance in response to various rates of nitrogen (N) and phosphorus (P) fertilizers. The experimental design in this study was Randomised Complete Block Design (RCBD) which involved 9 treatments; T1(5.2 g urea/plant + 11.2 g CIRP/plant), T2 (5.2 g urea/plant + 16.2 g CIRP/plant), T3 (5.2 g urea/plant + 21.2 g CIRP/plant), T4 (10.2 g urea/plant + 11.2 g CIRP/plant), T5 (10.2 g urea/plant + 16.2 g CIRP/plant), T6 (10.2 g urea/plant + 21.2 g CIRP/plant), T7 (15.2 g urea/plant + 11.2 g CIRP/plant), T8 (15.2 g urea/plant + 16.2 g CIRP/plant) and T9 (15.2 g urea/plant + 21.2 g CIRP/plant) with 3 replications. The result indicates that there was significant difference for the application of various rates of N and P fertilizers on the height increment, girth increment, chlorophyll content, above ground dry weight (leaf and stem), below ground dry weight (root). Nevertheless, there were no significant differences on total dry weight of rubber seedlings. Besides that, this experiment showed that the application of T2 (2.0 g urea/plant and 7.5 g CIRP/plant) gave much higher value of nutrient content for nitrogen, phosphorus, potassium, calcium and magnesium in the leaf tissues than the control T1 (2.0 g urea/plant and 2.5 g CIRP/plant). This may indicate inadequate application rates of phosphorus at the control treatment (T1). The expected result from this study will be useful for rubber plantation industry especially in the nursery and to provide new information about fertilizer requirement. Treatment T2 with application of fertilizer rate 2.0 g urea/plant and 7.5 g CIRP/plant gave the best result in all parameters taken in this study. So, the rate 2.0 g urea/plant and 7.5 g CIRP/plant is recommended to the rubber seedlings in the nursery.